Analisis Diskursus Feminisme dalam Kebijakan Pemenuhan Hak Pekerja Perempuan di Sektor Informal di Indonesia - Tiffany Setyo Pratiwi; Muhammad Dede Puja Kusuma (Jurnal Sosial Humaniora Sigli, 2025)
ABSTRACTThis article analyzes the development of feminist discourse in policies to fulfill the rights of women workers in the informal sector in Indonesia. This research examines how gender approaches and women's rights are negotiated by various stakeholders. This research uses a qualitative literature study approach and Norman Fairclough’s critical discourse analysis framework. Text analysis of the Manpower Law Number 13 of 2003 and the Job Creation Law shows that there is no text "female informal workers" as a policy language clearly stated in the articles of the law. The dimensions of discourse practice, it was found that civil society organizations such as ILO (International Labour Organization) are the main actors in the feminist discourse that articulates gender-based violence as a key issue for women workers in the informal sector. Furthermore, in the dimension of social practice, the ideology of economic-oriented development has created unequal power relations regarding the bargaining position of women workers in the informal sector. This study concludes that gender policy language must be inclusive in the law, as it will have implications for the implementation of the protection of women workers' rights in the informal sector as legal subjects. Currently, this tends to be normative, weak, and limited.Keywords: Critical Discourse Analysis; Feminism; Female Informal Workers; Policy; Indonesia